61.4k views
3 votes
Third-degree, with zeros of −3, −1, and 2, and passes through the point (1,8).

1 Answer

4 votes

Answer:

y=-(x+3)(x+1)(x-2)=-x^3-2x^2+5x+6

Explanation:

If the zeros are:

x1=-3

x2=-1

x3=2

then the function is:

y = a (x-x1) (x-x2) (x-x3) = a (x+3) (x+1) (x-2)

y = a (x^3+2x^2-5x-6)

To find the value for "a" we use the information that, if x=1, then y=8:

y = a (1+2-5-6) = a (-8) = 8 therefore a=-1

So:

y=-(x+3)(x+1)(x-2)=-x^3-2x^2+5x+6

User Chris Duncan
by
6.5k points